Study of Antioxidant Activity and Hepatoprotector Potential of Ethanol Extracts of Bark Mezzettia Parviflora Becc. on Liver Function of Wistar Strain Rats (Rattus Novergicus L.) - Masykur; Nurdin; Hakim, Lukman; Rosnizar; Sari, Widya; Husna, Asmaul; Ceriana, Ria (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the hepatoprotective potential of ethanol extract of Mezzetia Parviflora Becc. stem bark. (EEKBM) on serum glutamic oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT) levels in rats induced by toxic doses of paracetamol, as well as measuring the antioxidant concentration of EEKBM. The method used in this research was a Completely Randomized Design (CRD) consisting of 6 treatment groups and 4 replications. The test animals used were 24 individual male rats that were induced by hepatotoxicity with 1350 mg/kgBW of paracetamol on day 7, except for the normal control (K0) which was given distilled water. Test animals received treatment with distilled water in the negative control (K-), Hepa-Q as much as 11.34 mg/kgBW in the positive control (K+), EEKBM dose of 150 mg/kgBW (P1), dose of 300 mg/kgBW (P2), and a dose of 600 mg/kgBB (P3) for 14 days. Data on SGOT and SGPT levels were analyzed using Analysis of Variance (ANOVA) with a significance level of 5% with the Tukey test as a further test. The results of the study showed that there was a significant difference (P<0.05) in the effect of giving EEKBM on SGOT and SGPT levels. Based on the research results, it was concluded that a dose of 150 mg/kgBB EEKBM has hepatoprotective potential. Spectrophotometric measurement results show that EEKBM has an IC50 value of 96.308 μg/mL, categorized as strong antioxidant activity